PENGARUH METODE PEMBELAJARAN MAKE A MATCH BERBANTUAN READING GUIDE TERHADAP PENGUASAAN KONSEP PADA MATERI SISTEM PENCERNAAN MAKANAN PADA MANUSIA KELAS VIII SMPN 30 PEKANBARU TAHUN AJARAN 2014/2015 - Raudhah Awal (Lectura : Jurnal Pendidikan, 2015)
The purpose of this research is to know the effect of learning make a matchmethod assisted reading guide on students concept comprehension of the subjectmaters human digestive system in class VIII SMPN 30 Pekanbaru. This researchconducted on November 2014. The method of this research used was quasiexperiment with the nonequivalent pretest-posttest control group design. Thesampel of this research were students of VIII1 and VIII3 with using simple totalsampling technique. The data was analyzed in the from of t-test. The data wherecollected by pretest, posttest and observations. The mean of N-gain at experimentclass was 0,77 categorized at hight level, while at control class was 0,36Categorized at medium level. So it can be conduded that there was a significanteffect teacher learning and student’s activity of the subject matters humandigestive system in class VIII SMPN 30 Pekanbaru academic Year 2014/2015.